PrabotulinumtoxinA for the Treatment of Moderate-to-Severe Glabellar Lines in Adult Patients With Skin of Color: Post Hoc Analyses of the US Phase III Clinical Study Data. Issue 4 (April 2021) - Taylor, Susan C.; Grimes, Pearl E.; Joseph, John H.; Jonker, Anneke; Avelar, Rui L.
Abstract : BACKGROUND: Limited US clinical data are available on the use of aesthetic products in patients with skin of color (SOC). OBJECTIVE: To compare the efficacy and safety of prabotulinumtoxinA for the treatment of glabellar lines in patients with and without SOC. METHODS AND MATERIALS: Post hoc analyses were performed on the pooled population of all 492 patients treated with 20U prabotulinumtoxinA in the 2 US single-dose Phase III glabellar line clinical studies. Patients were grouped by Fitzpatrick skin Type: IV + V + VI (with SOC) versus I + II + III (without SOC). The primary efficacy end point was the proportion of responders with a ≥1-point improvement from baseline at maximum frown on the 4-point Glabellar Line Scale. Adverse events (AEs) were also summarized. RESULTS: Responder rates among patients with SOC ( n = 140) were lower than those without SOC ( n = 352), by 5.9% on average across all visits; at no time point were differences statistically significant. At Day 30, responder rates were 94.0% and 96.0%, respectively ( p = .401). Headache was the most common treatment-related AE, occurring in 12.1% and 8.2% of patients with and without SOC, respectively. CONCLUSION: A single dose of 20U prabotulinumtoxinA was well tolerated and similar in effectiveness in patients with and without SOC for the treatment of glabellar lines.